Animal welfare in poultry breeding - Bódi, László; Janbaz, Janan (Animal welfare, Ethology and Housing Systems (AWETH), 2005)
The author of the article brings up the question of defining animal welfare. Legislations ensuring animal welfare in housing technologies of laying hens (not improved cages, improved cages, alternative), and in liver and feather production are introduced. Rules of transportation, slaughtering, and other treatments (e.g. inserting wing tags) are overviewed as well.